Improving the Performance of Early Childhood Education Teachers in Developing Fine Motor Skills of Preschool Children at PAUD Mawar Ceria, Sukmajaya, Depok - Mulyanti, Fitrah (Pasundan Social Science Development, 2025)
This study aims to explore the improvement of Early Childhood Education (PAUD) teachers' performance in developing fine motor skills of young children at PAUD Mawar Ceria, Sukmajaya, Depok. Fine motor skills are crucial for children's development as they support various daily activities, learning processes, and cognitive growth. The research applies a qualitative approach with a focus on teacher strategies, classroom activities, and the learning environment. Data were collected through observation, interviews with teachers, and a review of relevant teaching materials and practices. The findings indicate that there has been a significant improvement in teachers' ability to foster fine motor skills through the use of creative and engaging activities, such as drawing, cutting, and playing with small objects. Additionally, teacher training sessions and collaboration with parents have contributed to enhancing the learning environment, making it more conducive for children’s fine motor development. This study highlights the importance of continuous professional development for teachers and the role of a supportive environment in optimizing children's motor skills development. The results suggest that a collaborative approach between teachers, parents, and the community can improve educational outcomes and overall child development.